2020
DOI: 10.1038/s41598-020-62860-9
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Protonation of the Calcium Pocket Enable Activation of the Calcium-Activated Chloride Channel Anoctamin-1 (TMEM16A)

Abstract: Anoctamin-1 (ANO1 or TMEM16A) is a homo-dimeric Ca 2+-activated cl − channel responsible for essential physiological processes. each monomer harbours a pore and a ca 2+-binding pocket; the voltage-dependent binding of two intracellular ca 2+ ions to the pocket gates the pore. However, in the absence of intracellular ca 2+ voltage activates TMEM16A by an unknown mechanism. Here we show voltage-activated anion currents that are outwardly rectifying, time-independent with fast or absent tail currents that are inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Phosphatidylinositol (4,5)-bisphosphate (PIP 2 ) was recently shown to play a critical role in regulating TMEM16A and TMEM16F ion channel rundown or desensitization ( Ta et al, 2017 ; De Jesús-Pérez et al, 2018 ; Ye et al, 2018 ; Le et al, 2019a ; Tembo et al, 2019 ; Yu et al, 2019 ). In addition, both intracellular and extracellular pH have also been reported to regulate endogenous CaCCs ( Arreola et al, 1995 ; Park and Brown, 1995 ; Qu and Hartzell, 2000 ) and heterologous expressed TMEM16A CaCCs ( Chun et al, 2015 ; Cruz-Rangel et al, 2017 ; Segura-Covarrubias et al, 2020 ). The Oh laboratory recently reported that intracellular protons can inhibit TMEM16A CaCC by competing with Ca 2+ on binding to the Ca 2+ binding sites instead of affecting intracellular histidine residues ( Chun et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatidylinositol (4,5)-bisphosphate (PIP 2 ) was recently shown to play a critical role in regulating TMEM16A and TMEM16F ion channel rundown or desensitization ( Ta et al, 2017 ; De Jesús-Pérez et al, 2018 ; Ye et al, 2018 ; Le et al, 2019a ; Tembo et al, 2019 ; Yu et al, 2019 ). In addition, both intracellular and extracellular pH have also been reported to regulate endogenous CaCCs ( Arreola et al, 1995 ; Park and Brown, 1995 ; Qu and Hartzell, 2000 ) and heterologous expressed TMEM16A CaCCs ( Chun et al, 2015 ; Cruz-Rangel et al, 2017 ; Segura-Covarrubias et al, 2020 ). The Oh laboratory recently reported that intracellular protons can inhibit TMEM16A CaCC by competing with Ca 2+ on binding to the Ca 2+ binding sites instead of affecting intracellular histidine residues ( Chun et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…C. Le et al ., 2019; Tembo et al ., 2019; Yu et al ., 2019). In addition, both intracellular and extracellular pH have also been reported to regulate endogenous CaCCs (Arreola, Melvin and Begenisich, 1995; Park and Brown, 1995; Qu and Hartzell, 2000) and heterologous expressed TMEM16A CaCCs (Chun et al ., 2015; Cruz-Rangel et al ., 2017; Segura-Covarrubias et al ., 2020). The Oh laboratory recently reported that intracellular proton can inhibit TMEM16A CaCC by competing with Ca 2+ on binding to the Ca 2+ binding sites instead of affecting intracellular histidine residues (Chun et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the Ca 2+ -activated chloride channels TMEM16A and TMEM16B do not contribute to passive membrane properties of mouse VSNs and do not alter major voltage-gated inward and outward currents in the range from −100 up to +40 mV. As TMEM16A can also be activated by high positive voltages in absence of intracellular Ca 2+ ( Xiao et al, 2011 ; Segura-Covarrubias et al, 2020 ), these results show that TMEM16A does not alter passive properties at membrane potentials up to +40 mV.…”
Section: Resultsmentioning
confidence: 75%